Ethics and society in Nigeria : identity, history, political theory - Wariboko, Nimi, 1962- (University of Rochester Press, 2019)
Offers a radical political interpretation of history that generates fresh insights into the emancipatory potential of ordinary Nigerians and their precolonial cultural institutions.
Keywords: Social ethics -- Nigeria.; Group identity -- Nigeria.; Political corruption -- Nigeria.; Nigeria -- Politics and government.; Nigeria -- Religion.; Identité collective -- Nigeria.; Corruption (Politique) -- Nigeria.; Nigeria -- Politique et gouvernement.; PHILOSOPHY -- Ethics & Moral Philosophy.; PHILOSOPHY -- Social.; HISTORY -- Africa -- West.; Group identity; Political corruption; Politics and government; Religion; Social ethics; Nigeria; Boston University.; Democratic Republicanism.; Emancipatory Politics.; Ethics.; Historical Identity.; History.; Human Flourishing.; Identity.; Moral Exemplars.; Myth.; Nigeria's Predicament.; Nigeria.; Nigerian Pentecostalism.; Nimi Wariboko.; Political Development.; Political Philosophy.; Political Theory.; Precolonial Cultural Institutions.; Religion.; Societal Transformation.; Society.; Socio-Ethical Identity.; Walter G. Muelder Professor of Social Ethics.